2008
DOI: 10.3892/mmr_00000059
|View full text |Cite
|
Sign up to set email alerts
|

Choline by magnetic spectroscopy and dynamic contrast enhancement curve by magnetic resonance imaging in neoadjuvant chemotherapy for invasive breast cancer

Abstract: Abstract. This study investigated the relationship between choline by magnetic resonance spectroscopy (MRS) and late enhancement curves by dynamic magnetic resonance imaging (DMRI) in determining therapeutic response to neoadjuvant chemotherapy (NAC) among invasive breast cancer patients. Subjects comprised 21 women (22 breasts) with biopsyconfirmed invasive breast cancer (mean age 54 years) who underwent MRS with choline and gadolinium-enhanced DMRI at 1.5 T before and after NAC. Choline signals on MRS were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Elevated tCho concentration was previously reported in many studies in malignant neoplasms [19][20][21]. The composite Cho resonance reflects the abnormal cellular proliferation and is considered as a biomarker of the rapid growth rate of malignant tumours that can be assessed in association with tumour size to achieve better diagnostic accuracy [22,23]. Hence, all the pathologically proven malignant tumours (47 lesions) in the current study showed increased Cho levels before starting NAC.…”
Section: Discussionsupporting
confidence: 55%
“…Elevated tCho concentration was previously reported in many studies in malignant neoplasms [19][20][21]. The composite Cho resonance reflects the abnormal cellular proliferation and is considered as a biomarker of the rapid growth rate of malignant tumours that can be assessed in association with tumour size to achieve better diagnostic accuracy [22,23]. Hence, all the pathologically proven malignant tumours (47 lesions) in the current study showed increased Cho levels before starting NAC.…”
Section: Discussionsupporting
confidence: 55%
“…There are cases where no tCho can be measured before chemotherapy, which limits the clinical utility of the MRS technique. The tCho detection rate in the pretreatment cohort ranges between 60% and 100% . Thus, improvements to increase the sensitivity of MRS for measuring tCho would be needed.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…The tCho detection rate in the pretreatment cohort ranges between 60% and 100%. [99][100][101] Thus, improvements to increase the sensitivity of MRS for measuring tCho would be needed. tCho metabolite detection level could be decreased following several cycles of postchemotherapy in pathological responders.…”
Section: In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have correlated changes in ADC on DW-MRI with treatment response in breast cancer patients breast cancer diagnosis as well as for monitoring response to treatment during NAT. [65][66][67][68][69][70][71][72] Applications A recent clinical trial reported by Kumar et al 67 demonstrated that malignant breast tissues have elevated W-F levels compared with controls, and that breast cancers decreasing in size with NAT also exhibited decreasing W-F ratios. 67 In a separate clinical trial reported by Tozaki et al 71 using choline MRS in patients undergoing NAT, the reduction rates of choline were statistically significantly different between pathological responders and nonresponders after two treatment cycles, with positive and negative predictive values of choline MRS of 89% and 100%, respectively.…”
Section: Applicationsmentioning
confidence: 99%